Desurdir a lógica do gênero - Donini, Angela A (2010)
What mobilized me to write this thesis are certain daily situations that we live in our bodies that, when perceived by our senses, provoke friction and a desire to rupture with the logic of gender and its domination over the experience of sexuality. Without a guide, I explore the movements produced by these frictions that immanently and simultaneously provoke the modulation of sexuality in political, social, and subjective fields. The logic of gender depends on biopolitical action. This action is intensified and provoked by the normatization of sexuality, as well as an intense appropriation of life through pharmatechnologies. In the sex society, promoted and produced by biopower, we can note that there is a proliferation of discourses about this topic: it incessantly occupies social, political, and legislative spaces. This discursive production is part of the control mechanisms and censorship that act through the pair of cynicism - pity. The rupture of the control mechanisms related to gender and sexuality, brought about by complex operations of microterrorism, are the principal elements of the cartography of this trajectory. Therefore, this work seeks to weave connections that convene possibilities of transformation in the experience of sexuality and its insertion in the rights and political, economic, and social scenario